Adult literacy organisers in Ireland resisting neoliberalism. Issue 6 (15th June 2018) - O'Brien, Tom
Abstract : Purpose: The purpose of this paper is to explore the experiences and responses of ten adult literacy organisers (ALOs) from Dublin, Wicklow and Kildare to the growing influence of neoliberalism and the commodification of adult literacy as a skill and function of the economy. The research argues for a greater focus on literacy as a social practice concerned with equality and social justice, rooted in emancipatory and transformative adult education. Design/methodology/approach: A qualitative research methodology using in-depth unstructured interviews, underpinned by critical realism. Findings: While the ALOs sampled have developed strategies to resist the impact of neoliberalism, they are also struggling to sustain their resistance and nurture access to emancipatory and transformative adult literacy practices. Research limitations/implications: The research is limited in size, being a small sample study of ten ALOs. Practical implications: The research will inform policy discussions in advance of the new further education and training strategy, where adult literacy policy is situated. Originality/value: The paper gives unique and independent access to the voices of ALOs in Ireland and provides a small example of empirical evidence of the commodification and marketisation of adult literacy under neoliberalism.